Terrorism in History - Hoffman, Bruce (Journal of Conflict Studies, 2007)
Abstract The central question addressed in this collection is: in what circumstances did terrorism act as a "driver of history," exerting a major impact on international and national events, and why was it able to do so? To answer this question, this article focuses on three levels of analysis: first, using the assassination of the Archduke Franz Ferdinand in 1914 as a case study, it explores terrorism’s monumental power to change the course of history. The second, which takes as its reference point the case of the Fenian dynamiters’ campaign in Britain during the 1880s, examines terrorism as a tactical weapon that achieves profound changes in governmental organization and policy to counter this menace. Finally, it discusses terrorism as a strategic force, re-calibrating international politics and affairs, and catapulting to prominence (and to an extent, power) hitherto unknown or inconsequential movements, such as the Palestinian fedayeen after the 1967 Six Day War. Each of these offers an important lesson from the past for our understanding of terrorism today, namely, how what may appear to be completely new and novel in the present often has a significantly relevant historical precedent. Indeed, all three cases presaged some later, important development in terrorist tactics or strategy: in the first case, the emergence of state-sponsored terrorism; in the second, attacks on subways (in London) and other mass transit, that also led to the formation of new security forces in response to the threat; and third, the "cult of the insurgent" that has enormous resonance in Iraq, with bin Laden, and in America’s war on terrorism today.